2020
DOI: 10.1109/access.2020.3012878
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Objective Topological Optimization of an Electric Truck Frame Based on Orthogonal Design and Analytic Hierarchy Process

Abstract: The electric truck frame as a vital load-bearing component has aroused growing attentions due to its enormous potential in lightweight. However, few systematic studies have been performed on the multi-objective topological design of the frame attributable to its complexity on loading and conflicting objectives. This paper aims to develop a multi-objective topology optimization strategy of the electric truck frame based on the hybrid decision making method combining orthogonal test design (OTD) and analytic hie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…The results indicate that perform in discrete topology optimization can provide unambiguous and smooth structural boundaries. Jie Qiao et al (2020) illustrated the develop a strategy for optimizing the electric truck frame's topology that takes use of orthogonal test designs and the Analytic Hierarchy Process (AHP) [21]. While there has been some systematic study on the frame's multi-objective topological design has been restricted in scope owing to the complexity of loads and competing incentives.…”
Section: Literature Surveymentioning
confidence: 99%
“…The results indicate that perform in discrete topology optimization can provide unambiguous and smooth structural boundaries. Jie Qiao et al (2020) illustrated the develop a strategy for optimizing the electric truck frame's topology that takes use of orthogonal test designs and the Analytic Hierarchy Process (AHP) [21]. While there has been some systematic study on the frame's multi-objective topological design has been restricted in scope owing to the complexity of loads and competing incentives.…”
Section: Literature Surveymentioning
confidence: 99%
“…The comparison results showed that the proposed method is not much affected by the weighted sum method used and can deal with ill-load cases. Qiao, et al [22] developed a hybrid weight determination method that combines the AHP-based method and the orthogonal test-based method to achieve a balance between subjective judgement and objective calculation. The weight value is calculated for each load case, using the AHP-based method and the orthogonal test-based method respectively.…”
Section: Multi-objective Topology Optimization For Curved Arm Of Mult...mentioning
confidence: 99%
“…Hence, topology optimization of the billet tong is a typical topology optimization problem of a continuum structure with multiple loads or working conditions [15]. Since this problem exists in many practical applications, it has been investigated by using the homogenization method [16][17][18], the level-set method [19], the Solid Isotropic Material with Penalization (SIMP) method [20][21][22][23][24][25], the Rational Approximation of Material Properties (RAMP) method [26], the Independent Continuous and Mapping (ICM) method [27,28], the Evolutionary Structural Optimization (ESO) method [29], evolutionary algorithms (EA) [30,31] and a hybrid approach [32]. SIMP is popularly adopted, among others because of its theoretical simplicity and ease of implementation [11,33].…”
Section: Introductionmentioning
confidence: 99%
“…It facilitates subjective decision-making across diverse contexts and conditions (Cao et al 2020a, b;Sun et al 2023;Zhu et al 2020). Qiao (Qiao et al 2020) applied AHP to analyze the weights under multiple operating conditions for the chassis of a specific electric truck. Subsequently, through multi-objective topology optimization, they achieved significant improvements in material utilization and operational performance.…”
Section: Introductionmentioning
confidence: 99%